Pengaruh Perceived Risk Dan Online Customer Review Terhadap Keputusan Pembelian Melalui Kepercayaan Pada Pengguna Marketplace Di Kota Bekasi - Tazkiyatunnisa Anggraeni, Nadiya; Kresnamurti Rivai P, Agung; Aditya, Shandy (CV. Lafadz Jaya, 2023)
Currently, many marketplaces are starting to develop in Indonesia. Marketplace is an online intermediary that is used to build buying and selling activities and transactions between sellers and buyers. This involves a trilateral relationship between sellers, buyers and marketplace providers. The purpose of this study was to determine the effect of perceived risk and online customer review on purchasing decisions through trust in marketplace users in Bekasi City. The number of samples specified is a minimum of 135 samples consisting of 27 question items. Collecting data in this study using a questionnaire using Google Forms. Data analysis in this study used a multivariate analysis method using SPSS software version 22 and SEM (Structural Equation Model) with SmartPLS. The research results show that perceived risk has no effect on the trust variable. Meanwhile, online customer reviews have an effect on trust. The perceived risk variable on purchasing decisions shows insignificant results, online customer reviews show that the results influence purchasing decisions. While the trust variable on purchasing decisions, the results show no significant effect. Perceived risk has no effect on purchasing decisions through trust, and finally, online customer reviews have an effect on purchasing decisions through trust. This means that the better the consumer reviews and the trust that consumers experience, the higher the purchase decision of the Shopee marketplace consumers.